2023
DOI: 10.1515/jmbm-2022-0252
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of circular skirted footing on gypseous soil subjected to water infiltration

Abstract: Skirted footings are used to increase the final carrying capacity of shallow foundations resting on unstable soil and to decrease settling by limiting the soil beneath them. Skirted footings are utilized as an alternative to pile driving in poor strength soils at the top layer, such as gypseous soil, to save project costs and time spent installing piles while maintaining excellent performance. The settling of circular skirted footings resting on gypseous soil subjected to loading, infiltration, and collapsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A numerical test using FEM (GEO STUDIO) was carried out to study the effect of soil infiltration on circular-skirted footing placed on gypseous soil. The result showed that bearing capacity and settlement improved with increasing skirt length and the settlement under footing was the same and not differential [20].…”
Section: Introductionmentioning
confidence: 91%
“…A numerical test using FEM (GEO STUDIO) was carried out to study the effect of soil infiltration on circular-skirted footing placed on gypseous soil. The result showed that bearing capacity and settlement improved with increasing skirt length and the settlement under footing was the same and not differential [20].…”
Section: Introductionmentioning
confidence: 91%